The cinema of Steven Soderbergh : indie sex, corporate lies, and digital videotape - DeWaard, Andrew; Tait, R. Colin (Directors' cuts., 2013)
The industry's only director-cinematographer-screenwriter-producer-actor-editor, Steven Soderbergh is contemporary Hollywood's most innovative and prolific filmmaker. A Palme d'or and Academy Award-winner, Soderbergh has directed nearly thirty films, including political provocations, digital experiments, esoteric documentaries, global blockbusters, and a series of atypical genre films. This volume considers its slippery subject from several perspectives, analyzing Soderbergh as an expressive auteur of art cinema and genre fare, as a politically-motivated guerrilla filmmaker, and as a Hollywood insider. Combining a detective's approach to investigating the truth with a criminal's alternative value system, Soderbergh's films tackle social justice in a corporate world, embodying dozens of cinematic trends and forms advanced in the past twenty-five years. His career demonstrates the richness of contemporary American cinema, and this study gives his complex oeuvre the in-depth analysis it deserves.